基于多刀铣削过程的弧面分度凸轮建模方法 - 刘言松; 曹巨江; 贺炜 (Jixie chuandong)
The roller gear indexing cam milling process by using several cutters is simulated through secondary development technology of CAD software.The modeling method of roller gear indexing cam computer aided design is given.The example proves that,the method is correct and feasible,the modeling process of the roller gear indexing cam is greatly simplified.The basis of establishing the general CAD system of cam with complex working surface is provided.